Characteristics of Epstein-Barr virus activation of human B lymphocytes (The Rockefeller University Press, 1981)
Epstein-Barr virus (EBV) will infect at least every third cell if exposed in vitro to an extensively purified B cell population from human peripheral blood. About 10% of such infected cells will be driven into immunoglobulin synthesis and secretion, as judged by the indirect protein A plaque assay. The appearance of EB nuclear antigen, de novo DNA synthesis, and immunoglobulin secretion are linked phenomena accompanying infection as judged by viral dilution experiments, which yield kinetics of a one-hit order. Induction of immunoglobulin secretion in B cells by EBV requires de novo synthesis of DNA, and consequently, nontransforming EBV (P3HR1) will not induce immunoglobulin secretion and will also specifically block such induction from subsequently added EBV. The termination of immunoglobulin induction by EBV in short-term cultures appears to be T cell dependent.